Kazakhstan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper reviews economic developments in the Republic of Kazakhstan during 1993-97. During 1993-94, price liberalization was virtually completed, most of the restrictions on foreign trade were eliminated, and a new currency with a unified rate was introduced. At the same time, state orders were phased out and privatization initiated. Since early 1996, the authorities have accelerated privatization, extending it to many large enterprises. Kazakhstan has also taken major steps toward banking and financial sector reform, through withdrawal of bank licenses, bank consolidation, introduction and enforcement of prudential regulations, and enhanced supervision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet